Religious Traditions and Cultural Acculturation: A Global Bibliometric Mapping (2001–2025) - Dupi, Muhamad; Prajoko, Denisha Albania; Istiqomah, Nahdiyah (Balai Penelitian dan Pengembangan Agama Semarang, 2025)
The proposed research is expected to present a bibliometric mapping of the world research on religious traditions and cultural acculturation of the past 20 years (2001-2025). Using 324 publications indexed in the Scopus database, the analysis was conducted using VOSviewer software to explore the structure of publications, author collaboration networks, institutional contributions, key journals, and keyword co-occurrences. The results indicate that in 2015 and subsequent years, there was a high rise in academic interest in the topic, and the United States and the United Kingdom became the major contributors. Schools like Brandeis University and the University of California, Irvine, are important vehicles of the discourse. Other researchers, such as Thomas G. Kirsch and David Mosse, are intellectuals who connect research clusters. The most frequent keywords include “religious pluralism,” “religion,” and “religious identity,” grouped into five thematic clusters covering identity, multiculturalism, syncretism, and cultural adaptation. The history of keywords shows that in recent years, there is an increasing emphasis on cultural adjustment and interreligious relations. This paper affirms the interdisciplinary and wide-ranging approach to the research topic, as well as the interest of researchers in utilizing bibliometric techniques in integrating scattered literature and visualizing the history of the international scholarly pursuit.